Analysis of the Teacher's Role in Developing the Character Values of Group B Children in Imam Syafi'i's Ra Example - Alawiyah, Tuti; Rahayu, Eka Pamuji (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The focus of this study is to describe the role of teachers in developing students' character values, especially Islamic character in early childhood. While the purpose of the study is to describe the Role of Teachers as educators, mentors, and as models in Building Character Values in Early Childhood.The study uses a descriptive qualitative approach. The type of research is a case study. The data collection techniques are Observation, Interviews, and Documentation. The data analysis technique used in this study is Miles and Huberman data analysis, namely Data Condensation, Data Reduction, Data Display, and Conclusion Drawing/Verification. While for the validity of the data in this study using Triangulation Techniques and Source Triangulation.The results of this study are: 1) The role of teachers as educators in Developing Character Values in Early Childhood, especially group B at RA Telasan Imam Syafi'i Tanjung Lombok Utara is as a protector, companion, and servant for their students. Protecting, accompanying, and serving students is the obligation and responsibility of a teacher as an educator to realize character values related to God, parents, and themselves. 2) The role of teachers as mentors in developing character values in early childhood, especially group B at RA Telasan Imam Syafi'i Tanjung Lombok Utara is as a director, controller, monitor, guard, and reminder which in its implementation is to always accompany, direct, remind and guide students to have good behavior, character, and morals. As a mentor, teachers not only guide students from a physical aspect but also build good mentality, good behavior, and good morals. 3) The role of teachers as models/roles in developing character values in early childhood, especially group B at RA Telasan Imam Syafi'i Tanjung Lombok Utara is to provide good examples to children, implement behaviors that are in accordance with the guidance of the Qur'an and Sunnah, align words with actions and display a neat and polite appearance inside and outside school and class.